Occupational exposure in acute-care hospitals, can we ensure equity in treatment?. (30th September 2020) - Antinolfi, F; Brunelli, L; Malacarne, F; Cocconi, R; Brusaferro, S
Abstract: Background: Healthcare workers (HCWs) occupational exposure to vaccine-preventable diseases (VPDs) is a great challenge, especially for the risk of disease transmission to patients and general population. Our aim was to explore HCWs occupational exposure management within Friuli Venezia-Giulia (FVG) Region (Italy) in order to identify the most appropriate and equal strategies. Methods: In December 2019 we collected data from the 7 acute-care hospitals of FVG. Total number of employees, methods to investigate on potential exposure to VPDs, immunity assumptions and management of occupational exposure were investigated. Results: We obtained data from all FVG hospitals, for a total of 14, 002 employees (average 2, 000; range 551-4, 336), including 12, 557 HCWs (average 1, 794; range 467-3, 922). Four hospitals also include students, being academic centers (2) or research institutions (2). All hospitals conduct potential exposure investigation among HCWs, including patients, caregivers, visitors, non-HCW employees, but students are considered in 6/7 hospitals. Immunity of exposed subjects is assumed based on vaccination evidence or serological positivity. Exclusion from work is prescribed to exposed susceptible HCWs in 5/7 hospitals, while workers re-allocation to lower risk wards is required in 4 hospitals; in 2 cases HWCs are asked to wear a mask during their shift. When appropriate, 2 hospitals administer immunoglobulin, whereas a specific procedure for susceptible HCWs exposure was not always available. In 6 cases the exposure of non-HCWs subjects is notified to the occupational doctor or worker manager, and in 1 case serological positivity is directly tested. Conclusions: There is heterogeneity in the management of VPDs occupational exposure within FVG, in particular regarding the surveyed categories and the actions required to the exposed subjects. The evaluation of potential adverse outcomes on patients would contribute in designing a more effective preventive strategy. Key messages: The adoption of different strategies in the HCWs occupational exposure management could result in potential treatment inequality. Exploring occupational exposure management strategies adopted in hospitals is fundamental to standardize practices.